The More Doctors Program in remote areas: the experience of the Special Supervision Group in Pará, Brazil - Raphael Augusto Teixeira de Aguiar; Harineide Madeira Macedo (Faculdade de Medicina de Botucatu (Unesp), 2019)
Abstract The More Doctors Program encompasses an academic supervision carried out by supervisory institutions that have signed an agreement with the Ministry of Education (MEC). Academic supervision is part of the educational offers and implies periodic and regular visits to participant doctors. However, due to the difficulties of some institutions in the North region to fulfill their responsibilities under the Project More Doctors for Brazil, MEC created the Special Supervision Group (GES), which has been operating since 2014 in that region. This article records the GES experience in the state of Pará from January 2015 to May 2017. Its main contribution is to enable the provision of care for the population that inhabits a vast region where there is shortage of doctors, as the supervision of the professionals is mandatory and if it did not occur, the Program would not be allowed in Pará.